Physical victimization in prison: The role of mental illness - Blitz, Cynthia L.; Wolff, Nancy; Shi, Jing (International journal of law and psychiatry, 2008)
This study compares prison physical victimization rates (inmate-on-inmate and staff-on-inmate) for people with mental disorder to those without mental disorder in a state prison system. Inmate subjects were drawn from 14 adult prisons operated by a single mid-Atlantic State. A sample of 7528 subjects aged 18 or older (7221 men and 564 women) completed an audio-computer administered survey instrument. Mental disorder was based on self-reported mental health treatment ever for particular mental disorders. Approximately one-quarter of the sample reported some prior treatment for schizophrenia, bipolar disorder, depression, PTSD, or anxiety disorder. Rates of physical victimization for males with any mental disorder were 1.6 times (inmate-on-inmate) and 1.2 times (staff-on-inmate) higher than that of males with no mental disorder. Female inmates with mental disorder were 1.7 times more likely to report being physically victimized by another inmate than did their counterparts with no mental disorder. Overall, both males and females with mental disorder are disproportionately represented among victims of physical violence inside prison.